Learning geometry in a large-enrollment class: do Tangrams help in developing students' Geometric Thinking? - Nyet Moi Siew (2012)
Aims: 1. To investigate the students’ levels of geometric thinking while engaging in in-class tangram activities in a large-enrollment class; 2. To find out the student’s perception towards the use of tangrams in learning geometry.